Integrative computational analysis of transcriptional and epigenetic alterations implicates DTX1 as a putative tumor suppressor gene in HNSCC - Gaykalova, Daria A; Zizkova, Veronika; Guo, Theresa; Tiscareno, Ilse; Wei, Yingying; Vatapalli, Rajita; Hennessey, Patrick T; Ahn, Julie; Danilova, Ludmila; Khan, Zubair; Bishop, Justin A; Gutkind, J Silvio; et al. (Oncotarget, 2017)
Over a half million new cases of Head and Neck Squamous Cell Carcinoma (HNSCC) are diagnosed annually worldwide, however, 5 year overall survival is only 50% for HNSCC patients. Recently, high throughput technologies have accelerated the genome-wide characterization of HNSCC. However, comprehensive pipelines with statistical algorithms that account for HNSCC biology and perform independent confirmatory and functional validation of candidates are needed to identify the most biologically relevant genes. We applied outlier statistics to high throughput gene expression data, and identified 76 top-scoring candidates with significant differential expression in tumors compared to normal tissues. We identified 15 epigenetically regulated candidates by focusing on a subset of the genes with a negative correlation between gene expression and promoter methylation. Differential expression and methylation of 3 selected candidates (BANK1, BIN2, and DTX1) were confirmed in an independent HNSCC cohorts from Johns Hopkins and TCGA (The Cancer Genome Atlas). We further performed functional evaluation of NOTCH regulator, DTX1, which was downregulated by promoter hypermethylation in tumors, and demonstrated that decreased expression of DTX1 in HNSCC tumors maybe associated with NOTCH pathway activation and increased migration potential.
Keywords: epigenomika; senioři; nádory hlavy a krku; nádorové buněčné linie; signální transdukce; Cell Movement; Gene Expression Profiling; spinocelulární karcinom; senioři nad 80 let; Genes, Tumor Suppressor; výpočetní biologie; RNA interference; regulace genové exprese u nádorů; Cohort Studies; Middle Aged; mužské pohlaví; Head and Neck Neoplasms; Signal Transduction; tumor supresorové geny; RNA Interference; Adult; Cell Line, Tumor; ubikvitinligasy; integration; kohortové studie; Cluster Analysis; polymerázová řetězová reakce s reverzní transkripcí; Aged, 80 and over; Ubiquitin-Protein Ligases; ženské pohlaví; Humans; Gene Expression Regulation, Neoplastic; metylace DNA; HNSCC; pohyb buněk; expression; methylation; lidé středního věku; DNA Methylation; DTX1; Reverse Transcriptase Polymerase Chain Reaction; stanovení celkové genové exprese; dospělí; receptory Notch; Carcinoma, Squamous Cell; Computational Biology; Epigenomics; Aged; Female; Receptors, Notch; shluková analýza; lidé; Male